Merriam-Webster's intermediate dictionary - Merriam-Webster (Springfield, Mass Merriam-Webster, Incorporated, 2004)
Provides definitions, pronunciation, etymology, part of speech designation, and other appropriate information. Intended for use by students in grades six to eight
3
Keywords: English language -- Dictionaries